THE EFFECTS OF POLITICAL CRISES ON TURKEY'S FOREIGN TRADE: PASTOR BRUNSON CASE - Sürmen, Yunus Emre (Bursa Teknik Üniversitesi, 2019)
In the international arena, suppressive control of global powers and conflicts of interest are gradually increasing. Offical statements made by the governmental authorities of the countries and various imposed sanctions, result with political crisis. This situation affects the political and economic relations of countries of non-agreement. The decline of “trade”, one of the cornerstones of economy, affects not only the party countries of non-agreement but also other countries which have economic relations with them and also the other sectors. Indeed, Mavi Marmara crisis experienced between Turkey and Israel, the military plane crash crisis between Turkey and Russia and the priest Brunson crisis between Turkey and the US may be shown up as examples of this situation. Although the effects of the crisis have often had substantial negative effects on bilateral relations and the trade between the related countries, there have been cases of partial effect or no effect as well. Here in this study, it is concluded that in terms of Turkey’s foreign trade, the political crisis between Turkey-USA has resulted with minor effect.

Uluslararası arenada küresel güçlerin etkinliği ve çıkar çatışmaları günden güne artmaktadır. Ülkelerin resmi yetkilileri tarafından yapılan açıklamalar ve uygulanan çeşitli yaptırımlar çoğu zaman siyasi krizlerle sonuçlanmaktadır. Oluşan bu durum, anlaşmazlığa taraf ülkelerin siyasi ve ekonomik ilişkilerini etkilemektedir. Ekonominin temel yapı taşlarından biri olan “ ticaretin” azalması, sadece anlaşmazlığa taraf bu ülkeleri değil, aynı zamanda bu ülkelerin ekonomik ilişki içerisinde olduğu diğer ülkeleri ve sektörleri de etkilemektedir. Türkiye’nin İsrail ile yaşadığı Mavi Marmara krizi, Rusya ile yaşadığı uçak krizi ve ABD ile yaşadığı Rahip Brunson krizi bu duruma örnek olarak gösterilebilir. Krizler çoğu zaman ikili ilişkilerde ve iki ülke ticaretinde belirgin negatif etki yaratmasına rağmen,  kısmi etkilerinin olduğu veya hiç etkilemediği durumlar da olmuştur. İşte bu çalışma da, Türkiye ve ABD arasında yaşanan siyasi krizin, Türkiye’nin dış ticareti açısından kısmi etki ile sonuçlandığını ortaya koymuştur.
SİYASİ KRİZLERİN TÜRKİYE'NİN DIŞ TİCARETİNE ETKİSİ: RAHİP BRUNSON DAVASI